Effect of a nanocomposite containing ostrich eggshell on calvarium healing in the rabbit: a pathologic study - ALEMI, H; ASGHARI, A.; ABEDI, G.; AKBARZADEH, A.; MORTAZAVI, P. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of the current study was to determine effect of a nanocomposite containing ostrich eggshell (NCOE) on the calvarium healing in the rabbit. Fresh ostrich eggshell was ground (300-500 μm), treated in phosphate-containing solutions and sterilized by gamma irradiation. Fifteen New Zealand white adult male rabbits were used. Four full-thickness skull defects were created in the calvarium. The first defect kept unfilled (control). The second defect was filled with autograft bone. The third defect was filled using NCOE. The fourth defect was filled with mixture of the autograft+NCOE bone. At 30, 60 and 90 days after surgery animals were euthanized and tissue specimens were collected and stained with hematoxylin eosin and trichrome staining method. Microsections were examined to assess the extent and intensity of inflammation, calvarium formation status and foreign body reaction. According to the results, filling defect significantly increased in NCOE-treated rabbits compared to the control group at 30 and 60 days post-surgery (P<0.05). There a statistically significant difference between experimental groups compared to the control group at 30 and 60 days post-surgery (P<0.05) while no statistically significant differences were observed among autograft, NCOE, autograft+NCOE (P>0.05). Also, absorb material significantly decreased in NCOE and autograft+NCOE groups compared to the control group at 60 days post-surgery (P<0.05). The filling defect significantly increased in autograft, NCOE and NCOE+autograft groups compared to the control group at 90 days post-surgery (P<0.05). There was no significant difference on inflammation and absorb material among the groups at 90 days post-surgery (P>0.05). These results suggested NCOE+autograft has improved the rate of calvarium healing in rabbits.